Factors Influencing Consumers’ Purchase Intention Towards Green Home Appliances - Teoh, Chen Wei; Khor, Kok Chin; Wider, Walton (Frontiers in Psychology, 2022)
Purpose: The main purpose of this study is to investigate the effects of after-sales service, brand equity, environmental awareness, and product pricing on consumer purchase intention towards green home appliances. Design/methodology/approach: Data were collected from 120 citizens in Penang, Malaysia aged 18 to 60 via the convenient sampling method and analysed using partial least square structure equation modeling (SmartPLS). Findings: Results indicate that brand equity, environmental awareness and product pricing had a significant effect on consumer purchase intention towards green home appliances. However, after-sales service did not have any significant effect on consumer purchase intention. Research limitations/implications: This research helps home appliance manufacturers to better design marketing promotions, taking into consideration consumers’ focus on brand equity, environmental awareness and pricing. Originality/value: This study provides consumer insights for government agencies to construct better policies in order to increase the green home appliance penetration rate among citizens.